Pelatihan Instrumen Tiup Brass pada Unit Marching Band GNPM Kabupaten Mandailing Natal (SENDRATASIK UNP, 2023)
The research at this writing is to determine the brass instrument training system in the Marching Band Gita Nada Pratama Mandailing Natal unit. The purpose of this study was to see how to find out the procedures for training the Brass Instrument in the Marching Band Gita Nada Pratama Mandailing Natal unit. This research was conducted in December-February 2021. It is a qualitative descriptive study that reveals the current phenomenon. The group of brass instrument players in the Marching Band Gita Nada Pratama Mandailing Natal Unit is the object of research. The research location is the Youth and Sports Office of Mandailing Natal Regency. Techniques in collecting data using observation techniques, interview techniques, and documentation techniques.At the stage of the training process on the brass unit of the Marching Band Gita Nada Pratama Mandailing Natal, the initial preparation includes the recruitment process, introduction of tools, understanding of body position, blowing technique, lip position, and the technique of finding the schedule and place of practice. The last is the preparation of exercises which include apple activities, warming up, and giving song material. In the training process, the Marching Band unit did not apply a written evaluation system and did not give strict sanctions to members of the brass instrument training process for the Marching Band Gita Nada Pratama Mandailing Natal using training methods, lectures and demonstrations.